Pemberdayaan Optimalisasi Branding dan Pemasaran Digital Produk Lokal BUMDes Desa Bicak melalui TikTok, Website, dan Penguatan Identitas Visual Produk - Primaadi Airlangga; Munawarah Munawarah; Siti Sufaidah; Muhammad Fatich; Mutawakkil Alallah; Nisfu Laily Shofiatujidda; Purwatiningsih Purwatiningsih; Amanatus Salamah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2026)
Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises (BUMDes) emphasizes the strategic role of BUMDes in strengthening village economic independence and community welfare. Bicak Village, Trowulan District, Mojokerto Regency, has local product potential in the form of knitting, ecoprint, and accessories. However, the marketing process still faced several obstacles, including limited branding identity, lack of attractive visual promotion media, and suboptimal use of digital platforms. This community service activity aimed to strengthen branding and digital marketing capacity through participatory-collaborative methods involving BUMDes managers, vocational high school students majoring in visual communication design, PKK members, and local business actors. The program was attended by 50 participants consisting of 10 BUMDes administrators, 20 vocational students, 15 PKK members, and 5 local MSME actors. Activities included digital marketing socialization, TikTok content training, product photography workshops, development of logos, hangtags, brochures, and marketing websites. Evaluation was conducted through activity observations, pretest–posttest questionnaires, documentation of participants' practical work, reflective discussions, and participant feedback on the implementation of the training program. The results showed an increase in participants’ understanding of digital marketing from an average score of 58.4 to 84.6. In addition, TikTok promotional content, product photo, website catalog product, and branding media in the form of logos and hangtags were successfully produced and used by BUMDes. This program contributed to improving participants’ digital promotion skills and strengthening the branding identity of local products in Bicak Village